ISOLATION AND CHARACTERIZATION OF PLANT GROWTH PROMOTING BACTERIA ISOLATED FROM GARLIC (allium sativum). - Botelho, Gloria Regina; Leoncio, Mariane Da Rosa (Scientia Agraria, 2017)
Garlic has great economic and social importance in Santa Catarina. It is a demanding crop in nutrients, being necessary high amount of chemical fertilizers, increasing the cost of production and the environmental impact. An alternative to the use of inputs are Rizobacteria Promoting Plant Growth (RPCP). Among the RPCPs, the most studied genera are Azospirillum, Bacillus and Pseudomonas of the fluorescent group that have shown benefits for the growth of several plant species. In this context, isolates of RPCP obtained from the rhizosphere of garlic maintained in protected cultivation were phenotypically and genotypically characterized and a growth promotion test in vivo was carried out, in protected cultivation. The biochemical tests used for phenotypic characterization were glucose and sucrose fermentation, Methyl Red (MR), catalase production and urea hydrolysis. The potential of plant growth induction was also evaluated by analyzing the production capacity of IAA (Indol-Acetic Acid) and calcium phosphate solubilization in vitro. Twenty-seven isolates were obtained. For the biochemical tests, 21 isolates were able to ferment glucose and 26, sucrose. For the other tests, all isolates showed a positive reaction. As for the mechanisms of plant growth promotion, 81.5% and 66.6% of the isolates presented IAA production and phosphate solubilizing capacity, respectively. The in vivo growth promotion test using maize (Zea mays) as a model indicated that the tested isolates (EB02, EB16, EB14, EB26, EB23) showed similarity to the treatment with 100% recommended nitrogen fertilization. The isolates were identified by sequencing the 16S rRNA gene. Fourteen isolates (51, 85% of the collection) were identified as Bacillus subtillis, including those tested in planta. These microorganisms present potential for the promotion of plant growth.